Regulation function of MMP-1 downregulated by siRNA on migration of heat-denatured dermal fibroblasts. Issue 6 (2nd November 2017) - He, Xianghui; Dai, Jinhua; Fan, Youfen; Zhang, Chun; Zhao, Xihong
ABSTRACT: Cutaneous wound healing is a complex physiological process that requires the efforts of various cell types and signaling pathways and often results in thickened collagen-enriched healed tissue called a scar. Therefore, the identification of the mechanism of cutaneous wound healing is necessary and has great value in providing better treatment. Here, we demonstrated that MMP-1 inhibition could promote cell proliferation in dermal fibroblasts via the MTT assay. Meanwhile, we investigated cell migration by flow cytometry and tested type I collagenase activity. We found that MMP-1 inhibition promoted cell proliferation and inhibited cell migration and type I collagenase activity. In conclusion, our study demonstrated that MMP-1 might be a potential therapeutic target in cutaneous wound healing.